Malocclusion and bullying in school teenagers (Research, Society and Development, 2020)
The study aimed to evaluate the association between malocclusion and bullying in high school adolescents from public schools in Olinda / PE. The sample consisted of 236 students from 14 to 19 years old, of both sexes. Data collection occurred through the application of a questionnaire with questions regarding PeNSE-based sociodemographic characterization and bullying. Dental occlusion was classified according to Andrews. Data were tabulated using Epidata software and analyzed in STATA. Bivariate analysis was performed using Pearson's chi-square test (p ≤ 0.05) and logistic regression model. A total of 24.9% of adolescents reported being bullied. Most had normal occlusion (68.3%) and had no problems with right (90.8%), left (90.0%), bilateral (98.3%) or anterior open bite (93, 3%). However, a proportion of 42.5% of adolescents had malocclusion, being the most prevalent Class II. Malocclusion was not statistically significant associated with any type of bullying (p = 0.587). Given the above, the practice of bullying is not associated with the presence or absence of malocclusion. However, it is suggested that further studies be conducted given the importance of such a theme.